A simplified method to predict the local stress field and N-SIF of V-shaped notch. (July 2020) - Shen, Wei; Liang, Guiming; Li, Chunmei; Liu, Enqian
Highlights: A simple formula to evaluate the notch stress distribution and N-SIF was presented. The relationship equation between singular strength value ' as ' and mesh size was derived. The simple formula is applicable to both infinite plate model and typical welded joints. Abstract: The V-notch stress formula based on linear elastic theory shows that the notch stress at the corner tends to infinity due to stress singularity effect. In fact, infinite stress will not be obtained by the results of finite element analysis, and the stress results depend on the mesh size. Based on the concept of singular intensity value ' as ', this paper presents a simple formula to evaluate the notch stress distribution and notch stress intensity factor (N-SIF). The simple notch stress evaluation formula has higher fitting precision and practicability. Meanwhile, in order to analyze the influence of mesh size on notch stress, a series of stress results of notched specimens with different opening angles and crack depths are systematically analyzed and compared. On this basis, the relationship equation between singular strength value ' as ' and mesh size is derived, which provides a basis for accurately obtaining the N-SIF of V-notch under coarse mesh. After a series of verification, it is found that the result of fatigue strength evaluated by the simplified formula has a smaller scatter band.